Generation of human embryonic stem cell line expressing dCas9-TET1 fusion protein for epigenetic editing - Ji-Woo Kim; Seongyea Jo; Eun-Hye Kang; Ji Hyeon Ryu; Haneul Noh; Han-Jin Park; Hyemin Kim (Stem Cell Research)
CRISPR-based epigenome editing systems can induce site-specific transcriptional activation or repression of target genes. Ten-eleven translocation methylcytosine dioxygenase 1 (TET1) is a transcriptional activation effector involved in the cytosine demethylation of CpG dinucleotides in gene regulatory regions. In this study, we generated a human embryonic stem cell line that stably expresses catalytically dead Cas9 (dCas9) fused to the catalytic domain of TET1 via lentiviral transduction. This cell line can be used for locus-specific transcriptional activation in combination with single guide RNAs and serves as a valuable tool for epigenetic regulation in stem cell and organoid models.